2017
DOI: 10.2217/pgs-2016-0150
|View full text |Cite
|
Sign up to set email alerts
|

Atp-Binding Casette Transporter Expression in Acute Myeloid Leukemia: Association with in Vitro Cytotoxicity and Prognostic Markers

Abstract: This comprehensive analysis suggests ABCC1, ABCC3, ABCB6 and ABCA5 as probable targets which can be modulated for improving chemotherapeutic responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…The patients with unfavorable cytogenetics, FLT3-ITD and c-KIT mutations generally expressed statistically higher ABC transporters levels than did the other risk groups. In contrast Varatharajan et al (15) had proposed that the expression of ABCB1 and ABCG2 was significantly lower in FLT3-ITD mutated AML patients compared with FLT3-ITD negative patients. In their study, the authors reported that the expression of ABCB1 and ABCG2 was markedly higher in NPM1-mutated patients than in unmutated patients, yet our study did not find any statistical differences between the expression levels of ABC transporters in NPM1-mutated and unmutated cases, except regarding ABCC4.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The patients with unfavorable cytogenetics, FLT3-ITD and c-KIT mutations generally expressed statistically higher ABC transporters levels than did the other risk groups. In contrast Varatharajan et al (15) had proposed that the expression of ABCB1 and ABCG2 was significantly lower in FLT3-ITD mutated AML patients compared with FLT3-ITD negative patients. In their study, the authors reported that the expression of ABCB1 and ABCG2 was markedly higher in NPM1-mutated patients than in unmutated patients, yet our study did not find any statistical differences between the expression levels of ABC transporters in NPM1-mutated and unmutated cases, except regarding ABCC4.…”
Section: Discussionmentioning
confidence: 84%
“…A recent study of 123 AML patients showed that patients with lower expression of the ABCB1 and ABCC1 genes had better OS and DFS compared with patients who had high expression of these genes (15). The predictive role of ABCC4 has been addressed in childhood AML (16).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has lately been suggested as a cholesterol transporter in the brain, connected to amyloid-β peptide generation and Alzheimer’s disease, 40 and has been associated with the progression of acute myeloid leukemia. 41 The tight regulation of transporting substances across membranes ensures survival under challenging conditions and thus facilitates adaptation to new environments. Therefore, it seems rather not surprising to find members of the ABC1 subfamily stably expressed under altered gravity, which ultimately may be a new environmental condition that cells might have to adapt to.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to AML, cell culture experiments demonstrated that AML cells are able to upregulate through epigenetic mechanisms the expression of a number of transporter proteins [53]. The mRNA expression for ABCA5, ABCB6, ABCC1, and ABCC3 has recently been reported to be upregulated in cells from 233 AML patients [54]. It is therefore likely that perturbed plasma lipid profiles in AML are related to intracellular changes in circulating AML cells through mechanisms involving multiple ABC transporters.…”
Section: Discussionmentioning
confidence: 99%